A Hydrolase‐Catalyzed Cyclization Forms the Fused Bicyclic β‐Lactone in Vibralactone. Issue 18 (9th March 2020) - Feng, Ke‐Na; Yang, Yan‐Long; Xu, Yu‐Xing; Zhang, Yue; Feng, Tao; Huang, Sheng‐Xiong; Liu, Ji‐Kai; Zeng, Ying
Abstract: Vibralactone is isolated from the basidiomycete fungus Boreostereum vibrans as one of the strongest lipase inhibitors. Its unusual β‐lactone‐fused bicycle is derived from an aryl ring moiety by an oxidative ring‐expansion prior to an intramolecular cyclization. Herein, we report the discovery of the cyclase VibC which belongs to the α/β‐hydrolase superfamily and is involved in the vibralactone biosynthesis. Biochemical and crystal studies suggest that VibC may catalyze an aldol or an electrocyclic reaction initiated by the Ser‐His‐Asp catalytic triad. For the aldol and pericyclic chemistry in living cells, VibC is a unique hydrolase performing the carbocycle formation of an oxepinone to a fused bicyclic β‐lactone. This presents a naturally occurring, new enzymatic reaction in both aldol and hydrolase (bio)chemistry that will guide future exploitation of these enzymes in synthetic biology for chemical‐diversity expansion of natural products. Abstract : The cyclization of an oxepinone (3 ) to form a fused bicyclic β‐lactone (1 ) proceeds by a ring‐opening aldol‐lactonization cascade or a pericyclic reaction driven by the Ser‐His‐Asp catalytic triad of the cyclase VibC from the basidiomycete Boreostereum vibrans .